1978
DOI: 10.5962/bhl.title.60768
|View full text |Cite
|
Sign up to set email alerts
|

An annotated bibliography of the muskellunge, Esox masquinongy (Osteichthyes: Salmoniformes) /

Abstract: PRINTED IN CANADA AT THE ALGER PRESS Literature references in this bibliography were drawn from a file accumulated over 24 years in the Department of Ichthyology and Herpetology at the Royal Ontario Museum, in conjunction with studies of esocid fishes. To those we have added references provided by a number of biologists and muskellunge anglers. In response to a growing interest in the welfare and pursuit of the muskellunge, and to increasing requests for access to the file, it seemed appropriate to publish thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Pike have both commercial and recreational value (Crossman & Casselman, 1987) and are of significant importance to local commercial fisheries and, particularly, the recreational fishing industry. Angling tourism is a growing economic sector in the region in question, with various professional guided fishing companies based in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Pike have both commercial and recreational value (Crossman & Casselman, 1987) and are of significant importance to local commercial fisheries and, particularly, the recreational fishing industry. Angling tourism is a growing economic sector in the region in question, with various professional guided fishing companies based in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Northern pike Esox lucius, the most widespread game fish in Minnesota (Pierce et al 1995), is commonly found across northern latitudes of Europe, Asia, and North America, where it has both commercial and recreational value (Crossman and Casselman 1987). Information about absolute population numbers of northern pike is difficult to obtain because of the intensive effort involved in obtaining accurate population estimates, especially for different sizes of fish.…”
mentioning
confidence: 99%
“…There are over thirty scientific reports mentioning or studying the phenomenon of cannibalism in pike, ESOX lucius, a typical predatory fish (Crossman & Casselman 1987, Raat 1988, both among early stages of the same cohort (e.g. Hunt & Carbine 1951, Giles et al 1986) and among individuals of different year classes (Grimm 1981, Craig & Kipling 1983.…”
Section: Introductionmentioning
confidence: 99%